2017
DOI: 10.1002/adfm.201702050
|View full text |Cite
|
Sign up to set email alerts
|

A Skin‐Inspired Integrated Sensor for Synchronous Monitoring of Multiparameter Signals

Abstract: Electronic skins, as the integration of multiple distinct sensors, have aroused broad interests owing to their great potential in sensing applications. However, problems including the interference between sensing components and the difficulty in synchronous monitoring are practically encountered when they are applied to mixed signals. In this work, efforts are devoted to trouble‐free technical strategies for laminating three sensors with different sensing abilities into a skin‐like electronic device. The use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 34 publications
0
71
0
1
Order By: Relevance
“…iii) The transport via ionic liquids within a composite of CNTs +[EMIM]Tf 2 N, as illustrated by Figure biii. This corresponds to the temperature dependent conducting mode based on ionic hopping of ionic liquids, captured by the Vogel–Tammann–Fulcher law . Under a given potential, the CNTs without direct contacts in the composite of CNTs +[EMIM]Tf 2 N would experience the charge transport of such a mode, resulting in an increase in temperature sensitivity of the composite of CNTs +[EMIM]Tf 2 N compared to pure CNTs coating.…”
Section: Resultsmentioning
confidence: 99%
“…iii) The transport via ionic liquids within a composite of CNTs +[EMIM]Tf 2 N, as illustrated by Figure biii. This corresponds to the temperature dependent conducting mode based on ionic hopping of ionic liquids, captured by the Vogel–Tammann–Fulcher law . Under a given potential, the CNTs without direct contacts in the composite of CNTs +[EMIM]Tf 2 N would experience the charge transport of such a mode, resulting in an increase in temperature sensitivity of the composite of CNTs +[EMIM]Tf 2 N compared to pure CNTs coating.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, the temperature sensor is not influenced by the external pressure stimulus and vice versa. Inspired by the human skin with configuration of epidermis, dermis, and hypodermis, a sandwich‐like sensing system is able to monitor signals of temperature, light, and pressure synchronously without mutual signal interference (Figure b) . To simplify the operation and integration, Zhu et al developed a bimodal sensor composed of two sinuous platinum (Pt) ribbons on a flexible polyimide substrate rather than multiple layers adopted by the foregoing mentioned examples .…”
Section: Multifunctional Skin‐interfaced Wearable Devicesmentioning
confidence: 99%
“…I, Epidermis corresponds to light/temperature sensor; II, Dermis corresponds to pressure sensor; III–IV, Hypodermis corresponds to Temperature sensor and thermal insulating layer. Reproduced with permission . Copyright 2017, John Wiley & Sons.…”
Section: Multifunctional Skin‐interfaced Wearable Devicesmentioning
confidence: 99%
“…The exponential technological growth during the 4IR has led to development of various systems, such as artificial electronic skin (e-skin), a transparent and flexible material capable of sensing external stimuli akin to the human somatosensory system [2][3][4] . Such electronic skins could allow one to cyber-physically interact with the environment via changes in temperature, humidity, infrared light intensity, etc 5,6 . In the near future, e-skin-laden clothing is expected to facilitate not only the acquisition of information about one's surroundings but also monitoring and digitalization of an individual's physical conditions.…”
mentioning
confidence: 99%
“…Nevertheless, it should be emphasized that most prior multifunctional sensors are restricted to only single or double functionality, designed for sensing pressure 8,9 , temperature 10,11 , proximity 4,12 , or pressure-temperature combinations 3,13 . Even though several recent studies have reported triple-functional or over-triple-functional sensors developed by applying various nanomaterials and fabrication techniques 6,[14][15][16] . Such sensors generally suffer from issues such as severe restrictions in transparency and efficiency of the fabrication process, which hinder their use as a practical and human-friendly e-skin.…”
mentioning
confidence: 99%